Synthesis and Spectral Analysis of Some Ru(III) Complexes of Azodyes Derived from 1-Phenyl-2,3-dimethyl- 4-amino pyrazol-5-one - HARIKUMARAN NAIR, M.L.; MARIAMMA, A.T. (Asian Journal of Chemistry, 2010)
Eight novel complexes of the azodyes 2,3-dimethyl-1-phenyl-4-(2-hydroxy-5-methyl phenyl azo)-pyrazol-5-one (cresol azo antipyrine CAAP) and 2,3-dimethyl-1-phenyl-4-(2,4-dihydroxyphenylazo) pyrazol-5-one (resorcinol azo antipyrine RAAP) have been synthesised and characterized by elemental analysis, IR, electronic, ESR and NMR spectra, magnetic, conductance measurements and cyclic voltammetric studies. The ligands are found to behave in a neutral bidentate manner. All the complexes are non electrolytes with octahedral geometry having general formulae [RuCl2X(PPh3) (CAAP)] and [RuCl2X(PPh3) (RAAP)] where X = Cl, NCS, NO3 or ClO4. The X-ray powder diffraction patterns of one of the complexes has also been examined and found to be orthorhombic with unit cell dimensions a = 16.0189 Å, b = 11.4826 Å and c = 7.6652 Å. The electrochemical behaviour of one of the complexes is followed using cyclic voltammetry.